Design and implementation of a domestic disinfection robot based on 2D lidar - Chao, Zhuoran (My University, 2021)
In the battle against the Covid-19, the demand for disinfection robots in China and other countries has increased rapidly. Manual disinfection is time-consuming, laborious, and has safety hazards. For large public areas, the deployment of human resources and the effectiveness of disinfection face significant challenges. Using robots for disinfection therefore becomes an ideal choice. At present, most disinfection robots on the market use ultraviolet or disinfectant to disinfect, or both. They are mostly put into service in hospitals, airports, hotels, shopping malls, office buildings, or other places with daily high foot traffic. These robots are often built-in with automatic navigation and intelligent recognition, ensuring day-to-day operations. However, they usually are expensive and need regular maintenance. The sweeping robots and window-cleaning robots have been put into massive use, but the domestic disinfection robots have not gained much attention. The health and safety of a family are also critical in epidemic prevention. This thesis proposes a low-cost, 2D lidar-based domestic disinfection robot and implements it. The robot possesses dry fog disinfection, ultraviolet disinfection, and air cleaning. The thesis is mainly engaged in the following work: The design and implementation of the control board of the robot chassis are elaborated in this thesis. The control board uses STM32F103ZET6 as the MCU. Infrared sensors are used in the robot to prevent from falling over and walk along the wall. The Ultrasonic sensor is installed in the front of the chassis to detect and avoid the path's obstacles. Photoelectric switches are used to record the information when the potential collisions happen in the early phase of mapping. The disinfection robot adopts a centrifugal fan and HEPA filter for air purification. The ceramic atomizer is used to break up the disinfectant's molecular structure to produce the dry fog. The UV germicidal lamp is installed at the bottom of the chassis to disinfect the ground. The robot uses an air pollution sensor to estimate the air quality. Motors are used to drive the chassis to move. The lidar transmits its data to the navigation board directly through the wires and the edge-board contact on the control board. The control board also manages the atmosphere LEDs, horn, press-buttons, battery, LDC, and temperature-humidity sensor. It exchanges data with and executes the command from the navigation board and manages all kinds of peripheral devices. Thus, it is the administrative unit of the disinfection robot. Moreover, the robot is designed in a way that reduces costs while ensuring quality. The control board’s embedded software is realized and analyzed in the thesis. The communication protocol that links the control board and the navigation board is implemented in software. Standard commands, specific commands, error handling, and the data packet format are detailed and processed in software. The software effectively drives and manages the peripheral devices. SLAMWARE CORE is used as the navigation board to complete the system design. System tests like disinfecting, mapping, navigating, and anti-falling were performed to polish and adjust the structure and functionalities of the robot. Raspberry Pi is also used with the control board to explore 2D Simultaneous Localization and Mapping (SLAM) algorithms, such as Hector, Karto, and Cartographer, in Robot Operating System (ROS) for the robot’s further development. The thesis is written from the perspective of engineering practice and proposes a feasible design for a domestic disinfection robot. Hardware, embedded software, and system tests are covered in the thesis.
Keywords: disinfection robot, lidar, ROS, SLAM